A Macromodel of Local Government Spending Behaviour in Norway - Audun Langørgen (Statistics Norway, Research Department, 1994)
A cooperative bargaining model is adapted to the setting of local government in Norway. Aggregate consumption, the capital stock and net financial wealth in the local public sector are endogenized. The origin of intertia in the model is ascribed to incrementalism or adjustment costs in the disagreement points of the Nash solution. Using the method of ordinary least squares, the model is estimated on sample data for the period 1973-1991. Different hypotheses regarding the disagreement point formation are tested, and the pure incrementalist model is encompassed by a more general partial adjustment model, implying that some other mechanism than just preservation of the status quo is operative. It is found that local government consumption, the capital stock and the net debt in the long run are stabilized relative to disposable income. Finally, results form model simulations are reported.
Keywords: C32; H72; H74; 330; Local government; consumption; investment; dynamic specification.